Educational Practice Outcomes Resulting from Intercultural Immersion Experience - Jones, Jacie; Walkowiak, Nicholas; Lee, Lynnea; Cheasick, Emily; Thesing-Ritter, Jodi M. (My University, 2019)
Culturally responsive curriculum should be integrated on a long-term basis that combines academic goals with anti-bias training. Educators, school administrators, and researchers must collaborate to integrate anti-bias education into their lesson plans and activities while monitoring the impact of these changes on student learning. Immersion experiences for educators can promote and inspire a change in their educational practices that can create a widespread transformation throughout the institution of education (McKown, 2005). The University of Wisconsin-Eau Claire has sponsored an educator scholarship to engage regional educators in a nine-day intercultural immersion experience with the goal of enhancing culturally responsive curriculum in regional schools. This immersion experience takes participants to sites of historical significance of the Civil Rights Movement. Educators participating in this scholarship are required to incorporate different aspects of the immersion experience into their educational practices to increase culturally responsive pedagogy. Twenty-eight past and current educator participants were invited by formal email to participate in individual interviews. This study provides a qualitative analysis of the various ways that educators integrate learning from the immersion experience into their own educational practices. Researchers analyzed the teacher perceptions of outcomes for students impacted by changing educational practices.
Color poster with text, charts, and maps.
Keywords: Civil Rights Pilgrimage (Eau Claire, Wis.); Immersion; Teachers; Posters